Politico-economic writings : an annotated reprint of 'Zeitungsartikel und Vorträge', edited by J.C. Nyíri. - Wittgenstein, Karl (John Benjamins Pub. Co., 1984)
An annotated reprint of""Zeitungsartikel und Vorträge""